Shortest path synthesis for Dubins non-holonomic robot - Xuan-Nam Bui; Boissonnat, J.-D.; Soueres, P.; Laumond, J.-P. (Robotics and Automation, '94 International Conference, 1994)
We calculate the partition of the configuration space R/sup 2//spl times/S/sup 1/ of a car-like robot, only moving forwards, with respect to the type of the length optimal paths. This kind of robot is subject to kinematic constraints on its path curvature and its orientation. Starting from the results on shortest paths, we give new optimality conditions on these paths, and compute the partition for any horizontal plane of the configuration space.< >